Curable composition and method for producing bonded structure

A curable epoxy-based adhesive composition with controlled water contact angle addresses thermal issues in bonding low heat-resistant materials, ensuring effective adhesion and device integrity without high-temperature heating.

JP7607450B2Active Publication Date: 2024-12-27TOKYO OHKA KOGYO CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020214982
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2024-12-27
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Conventional thermosetting adhesive materials used in laminated structures, such as organic EL devices, often cause thermal deformation or decomposition of low heat-resistant materials when heated at high temperatures.

Method used

A curable epoxy-based composition with specific structural units is used to form an adhesive layer that maintains good adhesive properties without high-temperature heating, achieving a water contact angle of 40° to 50° when heated at 80°C to 100°C and exposed to light.

Benefits of technology

The composition ensures effective bonding of low heat-resistant materials without thermal degradation, maintaining performance and structural integrity of devices like organic EL elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607450000001
    Figure 0007607450000001
  • Figure 0007607450000002
    Figure 0007607450000002
  • Figure 0007607450000003
    Figure 0007607450000003
Patent Text Reader

Abstract

To provide a curable composition which exhibits good adhesiveness without being heated at a high temperature, and a method for manufacturing a joint structure using the curable composition.SOLUTION: The curable composition is used for forming an adhesive layer bonding two or more adherends, at least one of which contains a low heat-resistant material. The curable composition contains an epoxy resin containing a constituent unit of a specific structure containing an epoxy group and gives a cured product having a water contact angle of 40-50° (inclusive) by heating at 80-100°C (inclusive) and exposure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition and a method for producing a bonded structure using the curable composition. [Background technology]

[0002] Conventionally, various thermosetting adhesive materials have been used to bond between layers in the formation of various elements having a laminated structure, etc. For example, Patent Document 1 proposes using benzocyclobutene, which is known to cure at 200° C. or higher, as a thermosetting adhesive layer in the manufacture of light-receiving elements including photodiodes. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-186317 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, various functional elements, such as organic EL elements (organic electroluminescence elements), often contain materials with poor heat resistance that are thermally deformed or thermally decomposed at high temperatures. For this reason, there is a demand for curable compositions that exhibit good adhesiveness without being heated at high temperatures for use in bonding adherends.

[0005] The present invention has been made in consideration of the above problems, and aims to provide a curable composition that exhibits good adhesion without heating at high temperatures, and a method for manufacturing a bonded structure using the curable composition. [Means for solving the problem]

[0006] The present inventors have found that the above problems can be solved by using a curable composition that is used to form an adhesive layer that bonds two or more adherends, and at least one of the two or more adherends contains an epoxy resin containing a structural unit of a specific structure containing an epoxy group as a curable composition containing a low heat-resistant material, and gives a cured product having a water contact angle of 40° to 50° by heating at 80° to 100° and exposure to light, and have completed the present invention. Specifically, the present invention provides the following.

[0007] A first aspect of the present invention is a curable composition for forming an adhesive layer that bonds two or more adherends, Contains an epoxy resin having a mass average molecular weight of 1,000 or more and 50,000 or less, The epoxy resin has the following formula (g1-1): [ka] (In formula (g1-1), R 61 , and R 62 each independently represents a divalent hydrocarbon group which may have a substituent, R 63 , and R 64 are each independently a hydrogen atom or an alkyl group. The repeating structure of the structural unit (g1) is represented by the following formula: At least one of the adhesive layers that bond two or more adherends includes a low heat resistant material; The curable composition gives a cured product having a water contact angle of 40° or more and 50° or less when heated at 80° C. or more and exposed to light.

[0008] A second aspect of the present invention is a method for producing a bonded structure, in which two or more adherends are bonded via an adhesive layer, and at least one of the two or more adherends includes a low heat resistant material, comprising: Applying the curable composition according to the first aspect to an adherend surface of at least one of two or more adherends to form a coating film; Heating the coating film at 80° C. or more and 100° C. or less, and then exposing the coating film to light to harden the coating film and form an adhesive layer; The manufacturing method includes bonding an adherend having an adhesive layer to another adherend. Effect of the Invention

[0009] According to the present invention, it is possible to provide a curable composition that exhibits good adhesion without heating at high temperatures, and a method for producing a bonded structure using the curable composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] ≪Curable composition≫ The curable composition is used to form an adhesive layer for bonding two or more adherends, at least one of which is a curable composition containing a low heat-resistant material. The curable composition contains an epoxy resin having a mass average molecular weight of 1000 to 50000. The epoxy resin is represented by the following formula (g1-1): [ka] (In formula (g1-1), R 61 , and R 62 each independently represents a divalent hydrocarbon group which may have a substituent, R 63 , and R 64 are each independently a hydrogen atom or an alkyl group. The compound has a repeating structure of a structural unit (g1) represented by the following formula: The curable composition containing the above epoxy resin gives a cured product having a water contact angle of 40° to 50° when heated at 80° C. to 100° C. and exposed to light.

[0011] As described above, the curable composition gives a cured product having a water contact angle of 40° or more and 50° or less when heated at 80° C. or more and 100° C. or less and exposed to light. A cured product having a water contact angle within the above range adheres well to adherends made of various materials.

[0012] Hereinafter, essential and optional components contained in the curable composition will be described.

[0013] <Epoxy resin> As described above, the curable composition contains an epoxy resin having a mass average molecular weight of 1000 or more and 50000 or less. The epoxy resin is represented by the following formula (g1-1): [ka] (In formula (g1-1), R 61 , and R 62 each independently represents a divalent hydrocarbon group which may have a substituent, R 63 , and R 64 are each independently a hydrogen atom or an alkyl group. The compound has a repeating structure of a structural unit (g1) represented by the following formula:

[0014] In the specification and claims of this application, an "epoxy resin" is a resin having two or more epoxy groups in one molecule. The mass average molecular weight of the epoxy resin is 1,000 or more and 50,000 or less, preferably 2,000 or more and 40,000 or less, more preferably 3,000 or more and 30,000 or less, and most preferably 3,000 or more and 20,000 or less. When the mass average molecular weight of the epoxy resin is within the above range, the cured product of the curable composition exhibits good adhesion to adherends made of various materials, and the curable composition has good coatability. In the specification and claims of this application, the "mass average molecular weight" is a polystyrene equivalent value measured by gel permeation chromatography. Hereinafter, the mass average molecular weight may be referred to as Mw.

[0015] [Structural unit (g1)] The epoxy resin has a repeating structure of the structural unit (g1) represented by the above formula (g1-1). In formula (g1-1), R 61 , and R 62 R is each independently a divalent hydrocarbon group which may have a substituent. 63 , and R 64are each independently a hydrogen atom or an alkyl group.

[0016] In formula (g1-1), R 61 , and R 62 each independently represents a divalent hydrocarbon group which may have a substituent. The term "substituted" for a divalent hydrocarbon group means that some or all of the hydrogen atoms in the divalent hydrocarbon group have been replaced with groups or atoms other than hydrogen atoms.

[0017] R 61 , and R 62 The divalent hydrocarbon group as may be an aliphatic hydrocarbon group, an aromatic hydrocarbon group, or a combination of an aliphatic hydrocarbon group and an aromatic hydrocarbon group. The term "aliphatic hydrocarbon group" refers to a hydrocarbon group that is not aromatic. The aliphatic hydrocarbon group may be a saturated aliphatic hydrocarbon group or an unsaturated aliphatic hydrocarbon group, and is preferably a saturated aliphatic hydrocarbon group.

[0018] R 61 , and R 62 Examples of the divalent aliphatic hydrocarbon group as include linear or branched aliphatic hydrocarbon groups and aliphatic hydrocarbon groups containing a ring in the structure. The linear or branched aliphatic hydrocarbon group preferably has 1 or more and 10 or less, more preferably 1 or more and 8 or less, even more preferably 1 or more and 5 or less, and most preferably 1 or 2 carbon atoms.

[0019] The linear aliphatic hydrocarbon group is preferably a linear alkylene group. Specific examples of the linear alkylene group include a methylene group, an ethylene group (ethane-1,2-diyl group), a trimethylene group, a tetramethylene group, and a pentamethylene group. As the branched aliphatic hydrocarbon group, a branched alkylene group is preferred. Specific examples of branched alkylene groups include alkylmethylene groups such as ethane-1,1-diyl group (-CH(CH3)-), propane-1,1-diyl group (-CH(CH2CH3)-), propane-2,2-diyl group (-C(CH3)2-), butane-2,2-diyl group (-C(CH3)(CH2CH3)-), pentane-2,2-diyl group (-C(CH3)(CH2CH2CH3)-), and pentane-3,3-diyl group (-C(CH2CH3)2-); alkyl ethylene groups such as the 2-ethylbutane-1,2-diyl group (-C(CHCH)-CH-); alkyl trimethylene groups such as the butane-1,3-diyl group (-CH(CH)CH-) and the 2-methylpropane-1,3-diyl group (-CHCH(CH)CH-); and alkyl tetramethylene groups such as the pentane-1,4-diyl group (-CH(CH)CHCHCH-) and the 2-methylbutane-1,4-diyl group (-CHCH(CH)CHCH-). The alkyl group in the alkyl alkylene group is preferably a straight-chain alkyl group having a carbon number of 1 to 5.

[0020] The linear or branched aliphatic hydrocarbon group (hereinafter also referred to as "chain aliphatic hydrocarbon group") may or may not have a substituent. Examples of the substituent include a fluorine atom, a fluorinated alkyl group having 1 to 5 carbon atoms, and an oxygen atom (=O).

[0021] Examples of the aliphatic hydrocarbon group that contains a ring in its structure include cyclic aliphatic hydrocarbon groups (groups in which two or more hydrogen atoms have been removed from an aliphatic hydrocarbon ring) and groups in which the cyclic aliphatic hydrocarbon group is bonded to the end of the aforementioned chain aliphatic hydrocarbon group or is present in the middle of the chain aliphatic hydrocarbon group. The cyclic aliphatic hydrocarbon group preferably has 3 or more and 20 or less, and more preferably has 3 or more and 12 or less, carbon atoms.

[0022] The cyclic aliphatic hydrocarbon group may be a polycyclic group or a monocyclic group. The monocyclic group is preferably a group obtained by removing two or more hydrogen atoms from a monocycloalkane having 3 to 6 carbon atoms. Examples of the monocycloalkane include cyclopentane and cyclohexane. The polycyclic group is preferably a group obtained by removing two or more hydrogen atoms from a polycycloalkane having 7 to 12 carbon atoms. Examples of the polycycloalkane include adamantane, norbornane, isobornane, tricyclodecane, and tetracyclododecane. The cyclic aliphatic hydrocarbon group may have a substituent, such as an alkyl group having from 1 to 5 carbon atoms, a fluorine atom, a fluorinated alkyl group having from 1 to 5 carbon atoms, and an oxygen atom (=O).

[0023] R 61 , and R 62 Examples of the aromatic hydrocarbon group as the aromatic ring include divalent aromatic hydrocarbon groups in which one hydrogen atom has been further removed from the aromatic hydrocarbon nucleus of a monovalent aromatic hydrocarbon group such as a phenyl group, a biphenyl group, a fluorenyl group, a naphthyl group, an anthryl group, or a phenanthryl group. The aromatic hydrocarbon group may have a substituent, such as an alkyl group having from 1 to 5 carbon atoms, a fluorine atom, a fluorinated alkyl group having from 1 to 5 carbon atoms and substituted with a fluorine atom, and an oxygen atom (=O).

[0024] R 61 , and R 62 When the divalent hydrocarbon group as represented by is a combination of an aliphatic hydrocarbon group and an aromatic hydrocarbon group, examples of the divalent hydrocarbon group include aralkyl groups such as benzyl group, phenethyl group, 1-naphthylmethyl group, 2-naphthylmethyl group, 1-naphthylethyl group, and 2-naphthylethyl group, in which one hydrogen atom has been further removed from the aromatic hydrocarbon nucleus. The divalent hydrocarbon group formed by combining an aliphatic hydrocarbon group and an aromatic hydrocarbon group may have a substituent, which may include an alkyl group having from 1 to 5 carbon atoms, a fluorine atom, a fluorinated alkyl group having from 1 to 5 carbon atoms and substituted with a fluorine atom, and an oxygen atom (=O).

[0025] R 61 , and R 62 As the alkyl group, a straight-chain aliphatic hydrocarbon group is preferable, a straight-chain alkylene group is more preferable, a straight-chain alkylene group having 1 to 5 carbon atoms is even more preferable, and a methylene group is most preferable.

[0026] In formula (g1-1), R 63 , and R 64 R is each independently a hydrogen atom or an alkyl group. 63 , and R 64 As the alkyl group, an alkyl group having 1 to 5 carbon atoms is preferable, a methyl group or an ethyl group is more preferable, and a methyl group is particularly preferable. R 63 , and R 64 Each of them is preferably a hydrogen atom or a methyl group.

[0027] A specific preferred example of the structural unit represented by formula (g1-1) is the structural unit represented by the following formula (g1-1-1). [ka]

[0028] The content of the structural unit (g1) represented by the above formula (g1-1) in the epoxy resin is not particularly limited as long as a cured product having a water contact angle of 40° or more and 50° or less can be formed using the curable composition by heating at 80° C. or more and 100° C. or less and exposure to light. The water contact angle of the cured product can be adjusted by adjusting the epoxy equivalent of the epoxy resin, by adding a small amount of a resin having a hydrophilic group that does not react with epoxy groups, such as a hydroxyl group or a polyoxyalkylene group, to the curable composition, or by adding a small amount of a resin having a hydrophobic group, such as a fluorinated alkyl group, to the curable composition.

[0029] The epoxy resin is preferably a homo / copolymer containing a structural unit (g1) represented by the above formula (g1-1). The epoxy resin is more preferably a homo / copolymer containing a structural unit (G) represented by the following formula (G-1). In formula (G-1), g6 and g7 each independently represent an integer of 1 or more and 5 or less, preferably an integer of 1 or more and 3 or less, more preferably 1. [ka]

[0030] The other structural units in the epoxy resin than the structural unit (g1) are not particularly limited, and examples thereof include structural units derived from the compounds described below. For example, diene compounds such as butadiene and isoprene; epoxy diene compounds such as epoxybutadiene and epoxyisoprene;

[0031] Since a cured product exhibiting a water contact angle within a desired range can be easily formed by heating at 80° C. or more and 100° C. or less and exposure to light, the content of the structural unit (g1) in the epoxy resin is preferably 5% by mass, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the total of all structural units in the epoxy resin. The upper limit of the content of the structural unit (g1) in the epoxy resin is preferably 100% by mass, and may be 80% by mass. The epoxy resin containing the structural unit (g1) can be obtained by a known method such as the Prilitsev epoxidation reaction. Alternatively, an epoxidizing agent may be reacted with the polybutadiene resin. As the epoxidizing agent, organic peracids such as peracetic acid, performic acid, perbenzoic acid, m-chloroperbenzoic acid, and perpropionic acid, and organic hydroperoxides such as hydrogen peroxide, tert-butyl hydroperoxide, and cumene hydroperoxide can be used.

[0032] The dispersity (Mw / Mn) of the epoxy resin is preferably from 1.0 to 6.5, more preferably from 1.5 to 6, and most preferably from 1.5 to 5. Here, "Mn" is the number average molecular weight.

[0033] The content of the epoxy resin in the curable composition is preferably 0.010% by mass or more and 0.050% by mass or less, more preferably 0.010% by mass or more and 0.040% by mass or less, and even more preferably 0.015% by mass or more and 0.035% by mass or less, based on the mass of the curable composition. By setting the content within the above range, a thin adhesive layer can be formed. In addition, the optical properties of the structure containing the formed cured product are well maintained.

[0034] When the curable composition contains the epoxy resin in an amount within the above range, the adhesion between the cured product of the curable composition and the adherend is good, and the coatability of the curable composition to the adherend is also good.

[0035] <Other ingredients> Examples of components other than the epoxy resin that may be contained in the curable composition include organic solvents, sulfur-containing organic compounds, nitrogen-containing organic compounds, surfactants, organic acids, photoacid generators, photobase generators, and colorants such as dyes and pigments.

[0036] In some cases, the cured product of the curable composition is required to have high transparency. In such cases, the curable composition preferably does not contain a colorant such as a dye or a pigment.

[0037] In this case, the cured product of the curable composition preferably exhibits a total light transmittance of 98% or more when the total light transmittance is measured using a cured product having a film thickness of 450 nm as a sample. In addition, when the adherend (low heat-resistant material) includes an organic light-emitting element, a light-emitting layer containing a light-emitting substance, an organic layer including a light-emitting layer containing a light-emitting substance, an electron transport layer, or a hole transport layer, the cured product of the curable composition may be required to have adhesiveness in a thin film. In this case, it is preferable that the curable composition does not contain the other components described above. In addition, the mass ratio of the epoxy resin to the mass of the solid content in the curable composition is preferably 90 mass% or more and 100 mass% or less, and more preferably 99 mass% or more and 100 mass% or less.

[0038] From the viewpoint of coating property, the curable composition preferably contains an organic solvent. The organic solvent is not particularly limited as long as it can dissolve the epoxy resin to form a homogeneous solution. For example, the organic solvent can be an organic solvent that is generally blended in various resist compositions. Specific examples of the organic solvent include lactones such as γ-butyrolactone; ketones such as acetone, methyl ethyl ketone, cyclohexanone, methyl-n-pentyl ketone, methyl isopentyl ketone, and 2-heptanone; polyhydric alcohols such as ethylene glycol, diethylene glycol, propylene glycol, and dipropylene glycol; glycol derivatives having an ester bond such as ethylene glycol monoacetate, diethylene glycol monoacetate, propylene glycol monoacetate, and dipropylene glycol monoacetate; monomethyl ethers, monoethyl ethers, and monopropyl ethers of the above-mentioned polyhydric alcohols or the above-mentioned glycol derivatives having an ester bond, monoalkyl ethers such as monobutyl ether and monoalkyl ethers; monophenyl ethers of the above-mentioned polyhydric alcohols or the above-mentioned glycol derivatives having an ester bond; cyclic ethers such as dioxane; esters such as methyl lactate, ethyl lactate (EL), methyl acetate, ethyl acetate, butyl acetate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, and ethyl ethoxypropionate; and aromatic organic solvents such as anisole, ethyl benzyl ether, cresyl methyl ether, diphenyl ether, dibenzyl ether, phenetole, butyl phenyl ether, ethylbenzene, diethylbenzene, pentylbenzene, isopropylbenzene, toluene, xylene, cymene, and mesitylene. The organic solvent may be used alone or in combination of two or more kinds.

[0039] The above components are mixed uniformly in the desired amounts to obtain a curable composition.

[0040] <Method for manufacturing joined structure> The method for producing a bonded structure includes bonding two or more objects to be bonded via an adhesive layer, wherein at least one of the objects to be bonded includes a low heat resistant material.

[0041] The method for producing the bonded body includes applying the curable composition to a surface to be bonded of at least one of two or more objects to be bonded to form a coating film; Heating the coating film at 80° C. or more and 100° C. or less, and then exposing the coating film to light to harden the coating film and form an adhesive layer; The method includes adhering an adherend having an adhesive layer to another adherend.

[0042] The above-mentioned curable composition gives a cured product having good adhesive properties when heated at a temperature of 80° C. or more and 100° C. or less and then exposed to light. Therefore, even if at least one of the two or more adherends contains a low heat-resistant material, a bonded structure can be produced while preventing performance deterioration, thermal decomposition, and deformation due to heat of the low heat-resistant material.

[0043] Here, the low heat-resistant material means an organic light-emitting element, a light-emitting layer containing a light-emitting substance, an organic layer containing a light-emitting layer containing a light-emitting substance, an electron transport layer, a hole transport layer, a resin material having a glass transition temperature of 100°C or lower, and / or a material that decomposes at 100°C. An organic light-emitting element is an organic light-emitting (electroluminescence, EL) element that is an electric field type light-emitting element, and is known to have its performance deteriorated by heat of 100° C. or more (JP 2009-117576 A). In general, the organic light-emitting element has a substrate, a light-emitting layer or an organic light-emitting layer for emitting light, electrodes, a sealing layer, and the like. The light-emitting layer containing a light-emitting substance is the light-emitting layer in the above-mentioned organic light-emitting device. The organic layer including the light-emitting layer containing a light-emitting substance is the organic light-emitting layer in the above-mentioned organic light-emitting element. The electron transport layer is the electron transport layer in the above organic light emitting device. The hole transport layer is the hole transport layer in the above organic light emitting device. A resin material having a glass transition temperature of 100° C. or lower is a resin material whose glass transition temperature determined by differential scanning calorimetry (DSC measurement) is 100° C. or lower. Moreover, a material that decomposes at 100° C. is a material whose decomposition onset temperature, determined by differential thermal analysis-thermogravimetry (TG-DTA measurement), is 100° C. or lower. The decomposition onset temperature is the temperature at which weight loss accompanying thermal decomposition begins.

[0044] Examples of resin materials having a glass transition temperature of 100° C. or less include polyethylene, polypropylene, polyvinyl chloride, ABS resin, polymethyl methacrylate, nylon 6, nylon 6,6, polyacetal resin, polyurethane resin, polylactic acid, EVA resin, polyvinylidene fluoride, polybutylene terephthalate resin, polyethylene terephthalate resin, PEDOT (poly(3,4-ethylenedioxythiophene)), PFO (polydioctylfluorene), etc. Also, acrylic resins described in JP 2010-204199 A can be used.

[0045] Since the above-mentioned low heat-resistant material is often used, the adherend is preferably a part of an organic EL element. For example, the part of the organic EL element as the adherend includes at least one of a light-emitting layer containing a light-emitting substance, an organic layer containing a light-emitting layer containing a light-emitting substance, an electron transport layer, a hole transport layer, and an organic light-emitting layer for the organic EL element.

[0046] The method of applying the curable composition to at least one of the adhesive surfaces of two or more adherends is not particularly limited. For example, when the adhesive surface is flat, the curable composition can be applied to the adhesive surface using a roll coater, a spray coater, a slit coater, or the like. In addition, when the shape of the adherend is a sheet or plate, and the curable composition is applied to the main surface of the sheet or plate-shaped adherend, a spinner can be used. When the surface to be adhered is curved or irregular, it is preferable to apply the curable composition using a spray coater. As long as application by a roll coater, spray coater, slit coater, spinner, or the like is possible, the adhesive surface may have irregularities.

[0047] The curable composition may be applied to one of the two adhesive surfaces that face each other when adhering objects to be adhered, or may be applied to both adhesive surfaces.

[0048] The thickness of the coating film is not particularly limited, but is appropriately determined depending on the thickness of the adhesive layer to be formed by curing the coating film.

[0049] After forming the coating film, the coating film is first heated to 80°C or more and 100°C or less. By heating at a temperature within this range, it is possible to partially proceed with curing of the coating film while preventing thermal decomposition and thermal deformation of the low heat-resistant material contained in the adherend. In addition, by heating the coating film at a temperature within the above range, it is easy to form an adhesive layer made of a cured product with a water contact angle of 40° or more and 50° or less by subsequent exposure to light.

[0050] The heating temperature is preferably from 80° C. to 95° C., more preferably from 85° C. to 95° C. The heating time is not particularly limited, but is preferably from 5 seconds to 1 hour, more preferably from 10 seconds to 30 minutes, even more preferably from 20 seconds to 10 minutes, and particularly preferably from 30 seconds to 5 minutes.

[0051] Next, the heated coating film is exposed to light. The exposure is carried out by irradiating it with active energy rays such as ultraviolet light and excimer laser light. Examples of the light source for the active energy rays include a low pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a chemical lamp, and an excimer laser generator. The amount of energy radiation to be irradiated varies depending on the composition of the positive photosensitive resin composition, but is, for example, 500 mJ / cm. 2 More than 5000mJ / cm 2 It is sufficient if it is below this level.

[0052] By the heating and exposure described above, an adhesive layer made of a cured product having a water contact angle of 40° to 50° is formed. Such a cured product has a certain number of hydroxyl groups generated by a reaction involving epoxy groups, and it is considered that the adherend is well bonded via the adhesive layer made of the cured product due to the interaction between the hydroxyl groups and the adherend. The thickness of the adhesive layer made of the formed cured product is, for example, 2 Å to 1000 nm, preferably 2 Å to 30 nm. When the low heat-resistant material includes an organic light-emitting element, a light-emitting layer containing a light-emitting substance, an organic layer containing a light-emitting layer containing a light-emitting substance, an electron transport layer, or a hole transport layer, the preferred thickness in terms of optical properties is 30 nm or less, 2 Å to 5 nm or less, more preferably 3 Å to 1 nm.

[0053] Next, the adherend having the adhesive layer is adhered to another adherend. Typically, in the adherend having the above-mentioned coating film, the coating film is heated and exposed to light to form an adhesive layer, and then the adherend is adhered to the adhesive layer. In addition, when the adherend has light-transmitting properties, two or more adherends may be joined via the above-mentioned coating film, and the coating film may be heated and exposed to light to form an adhesive layer that has developed adhesive properties between the adherends. EXAMPLES

[0054] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0055] Example 1 A curable composition was prepared by dissolving an epoxy homopolymer (Mw 10000) having a structural unit represented by the above formula (g1-1-1) in propylene glycol monomethyl ether acetate to prepare an epoxy polymer solution (epoxy polymer concentration 0.020% by mass). This curable composition was spin-coated on a glass substrate to form a coating film. The formed coating film was heated at 90°C for 60 seconds. The heated coating film was then exposed under the following conditions to form an adhesive layer with a thickness of 450 nm. The thickness of the adhesive layer was measured using a resist film thickness measuring device Nanospec (manufactured by Nanometrics). Using a Dropmaster700 (Kyowa Interface Science Co., Ltd.), a droplet of pure water (1.8 μL) was dropped onto the substrate surface, and the contact angle of water on the adhesive layer surface was measured 10 seconds after the drop. As a result, the contact angle of water was 41.5°. Furthermore, when the total light transmittance of the adhesive layer was measured in the measurement wavelength range of 0 to 2000 nm using MCPD-3000 (manufactured by Otsuka Electronics Co., Ltd.), the total light transmittance was 98% or more. <Exposure conditions> Exposure device: HMW-615N (low pressure mercury lamp manufactured by Oak Corporation) Exposure wavelength: G-line (436nm), H-line (405nm), I-line (365nm) mixed wavelength Exposure dose: 3000mJ / cm 2

[0056] Example 2 Exposure dose 1000mJ / cm 2 Except for changing the thickness of the adhesive layer to 450 nm, the adhesive layer was formed in the same manner as in Example 1. The contact angle of water on the adhesive layer was measured in the same manner as in Example 1, and the contact angle of water was 45.6°. The total light transmittance of the adhesive layer was measured in the same manner as in Example 1, and the total light transmittance was 98% or more.

[0057] Example 3 Exposure dose 2000mJ / cm 2 Except for changing the thickness of the adhesive layer to 450 nm, the adhesive layer was formed in the same manner as in Example 1. The contact angle of water on the adhesive layer was measured in the same manner as in Example 1, and the contact angle of water was 43.4°. The total light transmittance of the adhesive layer was measured in the same manner as in Example 1, and the total light transmittance was 98% or more.

[0058] Example 4 The curable composition used in Example 1 was spin-coated on a silicon substrate to form a coating film. The formed coating film was heated at 90°C for 60 seconds. The heated coating film was then exposed under the following conditions to form an adhesive layer with a thickness of 5 Å. The thickness of the adhesive layer was measured using a resist film thickness measuring device Nanospec (manufactured by Nanometrics). <Exposure conditions> Exposure device: HMW-615N (low pressure mercury lamp manufactured by Oak Corporation) Exposure wavelength: G-line (436nm), H-line (405nm), I-line (365nm) mixed wavelength Exposure dose: 3000mJ / cm 2

[0059] Next, a resin solution (concentration: 30% by mass, solvent: propylene glycol monomethyl ether acetate) of an acrylic resin (Mw; 9000) obtained by copolymerizing 4-hydroxyphenyl methacrylate, glycidyl methacrylate, and 3,4-epoxycyclohexylmethyl methacrylate in a molar ratio of 40:50:10 was spin-coated onto the adhesive layer to form a coating film, which was then heated at 90°C for 90 seconds to form a resin film with a thickness of 500 nm. A crosshatch test was performed on the formed resin film, in which cuts (crosshatching) were made to form a 10×10 square grid. The length of one side of the square grid was 1 mm. After the crosshatch test, the resin film was observed, but no peeling of the resin film was observed in the grid area. After the crosshatch test, a tape test was performed on the grid areas of the resin film in accordance with ASTM D3359-09e2. The resin film after the tape test was observed, but no peeling of the resin film was observed in the grid areas. Furthermore, after the tape test, the silicon substrate was immersed in an alkaline developer (aqueous solution of tetramethylammonium hydroxide with a concentration of 2.38% by mass) at room temperature for 60 seconds, followed by rinsing with pure water and air drying to perform an alkaline development test. After the alkaline development test, the resin film was observed, but no peeling of the resin film in the grid area or seepage of the developer through the gaps in the grid area was observed. Example 5 Exposure dose 1000mJ / cm 2 The same test as in Example 4 was carried out except for changing the above. As a result, no peeling of the resin film was observed after the crosshatch test, the tape test, or the alkaline development test, and only a very small amount of seepage of the alkaline developer was observed after the alkaline development test.

[0060] Comparative Example 1 The same test as in Example 4 was carried out, except that no exposure was carried out. As a result, no peeling of the resin film was observed after the crosshatch test, the tape test, or the alkaline development test, but significant penetration of the alkaline developer was observed after the alkaline development test.

[0061] Comparative Example 2 A test similar to that in Example 4 was carried out, except that no adhesive layer was formed and the resin film was formed directly on the silicon substrate. As a result, no peeling of the resin film was observed after the crosshatch test or the tape test, but significant peeling of the resin film was observed after the alkaline development test.

Claims

1. A curable composition for use in forming an adhesive layer for adhering two or more adherends, the adhesive layer comprising a cured product having a water contact angle of 40° or more and 50° or less by heating at 80° C. or more and 100° C. or less and exposure to light, wherein at least one of the two or more adherends comprises a low heat resistant material, and the curable composition comprises an epoxy resin having a mass average molecular weight of 1,000 or more and 50,000 or less, The epoxy resin is represented by the following formula (g1-1): 【Chemistry 1】 (In formula (g1-1), R 61 , and R 62 each independently represents a divalent hydrocarbon group which may have a substituent, R 63 , and R 64 are each independently a hydrogen atom or an alkyl group. The curable composition described above, which has a repeating structure of a structural unit (g1) represented by the following formula:

2. A curable composition used to form an adhesive layer for adhering two or more adherends, at least one of the two or more adherends comprising a low heat resistant material, the curable composition comprising an epoxy resin having a mass average molecular weight of 1,000 or more and 50,000 or less, the adherend containing the low heat-resistant material is at least one of an electron transport layer, a hole transport layer, and an organic light-emitting layer for an organic electroluminescence element, The epoxy resin is represented by the following formula (g1-1): 【Chemistry 2】 (In formula (g1-1), R 61 , and R 62 each independently represents a divalent hydrocarbon group which may have a substituent, R 63 , and R 64 are each independently a hydrogen atom or an alkyl group. The repeating structure of the structural unit (g1) is represented by the following formula: A curable composition which, when heated at 80° C. or more and 100° C. or less and exposed to light, gives a cured product having a water contact angle of 40° or more and 50° or less.

3. The curable composition according to claim 1 or 2, wherein a ratio of a mass of the epoxy resin to a mass of the curable composition is 0.010 mass% or more and 0.040 mass% or less.

4. 3. The curable composition according to claim 1, wherein a ratio of the number of moles of the structural unit (g1) to all structural units constituting the epoxy resin is 10 mol % or more.

5. The curable composition according to claim 1 , wherein the adherend containing the low heat resistant material is at least one of an electron transport layer, a hole transport layer, and an organic light emitting layer for an organic EL device.

6. The curable composition according to any one of claims 1 to 5, which gives a cured product having a total light transmittance of 98% or more as measured using a sample having a film thickness of 450 nm.

7. A method for producing a bonded structure, comprising: two or more adherends being bonded to each other via an adhesive layer; and at least one of the two or more adherends comprising a low heat resistant material, the method comprising the steps of: Applying the curable composition according to any one of claims 1 to 5 to an adherend surface of at least one of the two or more adherends to form a coating film; heating the coating film at 80° C. or more and 100° C. or less, and then exposing the coating film to light to harden the coating film and form the adhesive layer; and adhering the adherend having the adhesive layer to another adherend.

8. The method for manufacturing a bonded structure according to claim 7 , wherein the adhesive layer has a thickness of 30 nm or less.

9. 9. The method for producing a bonded structure according to claim 7 or 8, wherein the adherend containing the low heat-resistant material is at least one of a light-emitting layer containing a light-emitting substance for an organic EL element, an organic layer containing a light-emitting layer containing a light-emitting substance, an electron transport layer, a hole transport layer, and an organic light-emitting layer.

Citation Information

Patent Citations

  • Surface modifying material, resist pattern forming method and pattern forming method

    JP2011197425A

  • Method for controlling surface physical property of substrate

    JP2018056269A

  • Photo detector and manufacturing method of component

    JP2019186317A

  • Curable resin composition and electronic devices such as organic electroluminescence element using cured product thereof

    WO2016170893A1